Definition of the amount of heat released during metal cutting by abrasive grain and the contact temperature of the ground surface - Lebedev, Vladimir; Klimenko, Natalia; Chumachenko, Tatiana; Uryadnikova, Inga; Ovcharenko, Alexander (Eastern-European Journal of Enterprise Technologies, 2016)
The subject of the study is the process of heat generation during grinding of metals and alloys, and the object of the study − the definition of the amount of heat released during metal cutting by individual abrasive grains, the summation of heat flows from the individual grains and the formation of the power of the heat source in the contact area of the grinding wheel with the grinding part. It is shown that the model of the cutting part of the grain in the form of a ball is adequate to the grain cutting process and allows to define the cutting forces by the value of the grain deepening to the metal. Mathematical formulas reflecting the grain depth of penetration into the metal as it moves along the route were shown. It is shown that the metal temperature is increased considerably when moving the grain from the beginning to the end of the route, due to the increase of the penetration depth of the grain into the metal. The paper contains mathematical relationships that reflect changes in the mechanical characteristics of steels of different classes depending on the cutting speed and temperature, and the system of numerical calculation of the amount of heat given off by the grain at any section of the trajectory. It is shown that the tensile strength of the metal during cutting by grain is significantly reduced when movement of the grain from the beginning to the end of the track, which leads to “hardness alignment” in grinding various alloys. We give the mathematical relationships of the laws of formation of the total heat source with all the grains running in the contact range of the wheel and the workpiece, which gave the opportunity to calculate the contact temperature of grinding of any material, such as ironcarbon alloy. It is shown that the main contribution to the formation of thermal contact temperature value is made by the grains located at 3/5 length of the contact arc, measured from the end of the motion path. Defining this value makes it possible to determine the capacity of the thermal source generated by summing of the heat flows from the grains located in the contact area of the wheel with the workpiece, calculate the thermal stress of the grinding process, depending on the processing mode, and the grit size of the wheel and the material of grains. Knowledge of thermal stress of the grinding process makes it possible to design a treatment process so as to prevent contact grinding temperatures, causing the appearance of burn marks and cracks, dramatically reducing the strength, reliability and durability of machined parts.